COVID‐19 rapidly increases MDSCs and prolongs innate immune dysfunctions. Issue 10 (24th June 2022) - Schrijver, Irene T.; Théroude, Charlotte; Antonakos, Nikolaos; Regina, Jean; Le Roy, Didier; Bart, Pierre‐Alexandre; Chiche, Jean‐Daniel; Perreau, Matthieu; Pantaleo, Giuseppe; Calandra, Thierry; Roger, Thierry
Abstract : We used unsupervised immunophenotyping of blood leukocytes and measured cytokine production by innate immune cell exposed to LPS and R848. We show that COVID‐19 induces a rapid, transient upregulation of myeloid‐derived suppressor cells (MDSCs) accompanied by a rapid, sustained (up to 3 months) hyporesponsiveness of dendritic cells and monocytes. Blood MDSCs may represent biomarkers and targets for intervention strategies in COVID‐19 patients.